2013
DOI: 10.1371/journal.pone.0083013
|View full text |Cite
|
Sign up to set email alerts
|

Beauvericin Ameliorates Experimental Colitis by Inhibiting Activated T Cells via Downregulation of the PI3K/Akt Signaling Pathway

Abstract: Crohn's disease is a common, chronic inflammatory bowel condition characterized by remission and relapse. Accumulating evidence indicates that activated T cells play an important role in this disease. In the present study, we aimed to examine the effect of beauvericin, a natural cyclic peptide, on 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitis in mice, which mimics Crohn's disease. Beauvericin significantly reduced weight loss, diarrhea and mortality, accompanied with notable alleviation of macrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 48 publications
0
48
1
Order By: Relevance
“…So have Gammelsrud et al 88 shown that ENN B en BEA influenced the expression of various co-stimulatory molecules, indicating that ENN B as well as BEA, could disturb dendritic cell migration and interfere with the macrophage differentiation process, inhibit the initiation of a specific immune response, modulate cytokine secretion and change the orientation of an immune response. 84,89 Moreover, Wu et al 90 have demonstrated that BEA decreased serum levels of TNF-α and IFN-γ in mice with experimental colitis and suppressed T-cell proliferation and activation, leading to apoptosis of activated T cells and making BEA a novel drug candidate for the treatment of colonic inflammation, such as Crohn's disease. 90 Immunological skin cells can thus be considered as possible targets for these cyclic depsipeptides.…”
Section: Local Skin Concentrations and Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…So have Gammelsrud et al 88 shown that ENN B en BEA influenced the expression of various co-stimulatory molecules, indicating that ENN B as well as BEA, could disturb dendritic cell migration and interfere with the macrophage differentiation process, inhibit the initiation of a specific immune response, modulate cytokine secretion and change the orientation of an immune response. 84,89 Moreover, Wu et al 90 have demonstrated that BEA decreased serum levels of TNF-α and IFN-γ in mice with experimental colitis and suppressed T-cell proliferation and activation, leading to apoptosis of activated T cells and making BEA a novel drug candidate for the treatment of colonic inflammation, such as Crohn's disease. 90 Immunological skin cells can thus be considered as possible targets for these cyclic depsipeptides.…”
Section: Local Skin Concentrations and Effectsmentioning
confidence: 99%
“…84,89 Moreover, Wu et al 90 have demonstrated that BEA decreased serum levels of TNF-α and IFN-γ in mice with experimental colitis and suppressed T-cell proliferation and activation, leading to apoptosis of activated T cells and making BEA a novel drug candidate for the treatment of colonic inflammation, such as Crohn's disease. 90 Immunological skin cells can thus be considered as possible targets for these cyclic depsipeptides. Our results showed that application of 1 mg/ml after 24 h resulted in dermis concentrations up to 12.53 μM for intact and 32.70 μM for damaged skin, whereas for the epidermis this was 577.70 μM and 659.96 μM, respectively (ENN A).…”
Section: Local Skin Concentrations and Effectsmentioning
confidence: 99%
“…Crohn's disease is one of the chronic intestinal inflammation, characterized by remission and frequently relapsing, affecting the gastrointestinal tract mainly in mucosal and submucosal inflammation, with clinical symptoms such as diarrhea with passage of blood or mucus, abdominal pain and the loss of weight (Hollenbach et al, 2005). In Western countries, CD has a highly incidence of 27-48 cases in about 100,000 persons every year (Bernstein et al, 2006;Wu et al, 2013). Meanwhile, in recent years, CD has a continually increasing incidence in China (Zheng et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The number of mucosal activated CD4 T cells is closely related to the structural integrity of intestinal mucosa because activated T cells can interact with the intestinal epithelial cells and damage the structure of intestinal mucosa. [36] High levels of CD4 T cell aggregation and T cell infiltration have been observed in the intestinal tract of UC mice. [37] Deoxyschizandrin significantly reduced the level of DSS-induced mucosal T cell infiltration in the colon [Figure 3d], suggesting an inhibitory role of deoxyschizandrin in T lymphocyte aggregation and mucosal infiltration in UC.…”
Section: Discussionmentioning
confidence: 99%